2018
DOI: 10.1001/jamaoto.2018.1791
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Burden Associated With Late Lower Cranial Neuropathy in Long-term Oropharyngeal Cancer Survivors

Abstract: In this large survey study, OPC survivors with late LCNP reported worse cancer treatment-related symptoms, a finding suggesting an association between late LCNP and symptom burden. This research may inform the development and implementation of strategies for LCNP surveillance and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 25 publications
(61 citation statements)
references
References 44 publications
5
56
0
Order By: Relevance
“…Large and statistically significant differences in functional metrics by LCNP status also support our findings of high functional morbidity among LCNP cases. Our study results also support a previous survey analysis in this study population, which used complete case analysis of MDASI‐HN, with low attrition of cases due to missing data and demonstrated a strong impact of LCNP on swallowing, choking, mucus, fatigue, and voice symptoms …”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Large and statistically significant differences in functional metrics by LCNP status also support our findings of high functional morbidity among LCNP cases. Our study results also support a previous survey analysis in this study population, which used complete case analysis of MDASI‐HN, with low attrition of cases due to missing data and demonstrated a strong impact of LCNP on swallowing, choking, mucus, fatigue, and voice symptoms …”
Section: Discussionsupporting
confidence: 89%
“…However, another cohort study reported 14% incidence of LCNP in 10‐year survivors of HNC, suggesting that risk increases over time . Our previous report confirmed high symptom burden among OPC survivors who developed LCNP, with largest effect sizes (coefficient, 2.3 of 10) on swallowing‐related symptoms . This phenomenon is also clinically recognized, but previous work has failed to quantify the impact of LCNP on individual swallowing domains and functional metrics.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations